2011
DOI: 10.1002/job.665
|View full text |Cite
|
Sign up to set email alerts
|

Age and work‐related motives: Results of a meta‐analysis

Abstract: SummaryAn updated literature review was conducted and a meta-analysis was performed to investigate the relationship between age and work-related motives. Building on theorizing in life span psychology, we hypothesized the existence of age-related differences in work-related motives. Specifically, we proposed an age-related increase in the strength of security and social motives, and an age-related decrease in the strength of growth motives. To investigate life span developmental theory predictions about age-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
516
6
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(577 citation statements)
references
References 139 publications
(131 reference statements)
44
516
6
11
Order By: Relevance
“…Instead, they place more value on deriving meaning from life, establishing intimacy with others in the present, and developing a sense of belonging in the social environment. The basic premises of the theory were confirmed in research of social motivation in general (Lang and Carstensen 2002) and in the workplace (Kooij et al 2011). For example, Kooij et al (2011) performed a meta-analysis on age differences in work motivation and found that younger workers tend to place greater emphasis on knowledge gathering and career development, whereas older workers prioritize a sense of accomplishment, job security, and helping others.…”
Section: The Role Of Employee Age In Effects Of Csrmentioning
confidence: 73%
See 2 more Smart Citations
“…Instead, they place more value on deriving meaning from life, establishing intimacy with others in the present, and developing a sense of belonging in the social environment. The basic premises of the theory were confirmed in research of social motivation in general (Lang and Carstensen 2002) and in the workplace (Kooij et al 2011). For example, Kooij et al (2011) performed a meta-analysis on age differences in work motivation and found that younger workers tend to place greater emphasis on knowledge gathering and career development, whereas older workers prioritize a sense of accomplishment, job security, and helping others.…”
Section: The Role Of Employee Age In Effects Of Csrmentioning
confidence: 73%
“…After all, needs may differ strongly between employees. For example, needs, motives, and values are influenced by adult development and work experiences across the life span (Kooij et al 2011;Truxillo et al 2015). Given that CSR addresses various employee needs and motives, and that these needs and motives are partly determined by life span characteristics, one would expect the effects of CSR on employee satisfaction to be moderated by employee chronological age.…”
Section: The Effects Of Csr On Employee Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOC theory proposes that people's motivational focus and choice for allocation of core resources in their work life gradually shifts from a growth and development orientation in younger years to a maintenance and loss-reduction orientation later on (Kooij et al, 2013;Kooij, De Lange, Jansen, Kanfer, & Dikkers, 2011). Although SOC researchers have mostly used chronological age in their assessments, the underlying logic suggests it is people's perception about their age that drives effects on subsequent behavior.…”
Section: Average Relative Subjective Age and Average Individual Goalmentioning
confidence: 99%
“…In this latter study, however, mastery and performance goals were not examined along the approach-avoidance dimension. Research examining achievement goals along the career trajectory in adult populations is still sparse, though one line of evidence indicates that people in late adulthood are more likely than young adults to pursue mastery avoidance goals and strive toward maintenance and prevention of skill loss and decline in performance (Kooij et al, 2011;Senko and Freund, 2015).…”
Section: Introductionmentioning
confidence: 99%